2019
DOI: 10.3390/admsci9010010
|View full text |Cite
|
Sign up to set email alerts
|

Examining Customer–Brand Relationships: A Critical Approach to Empirical Models on Brand Attachment, Love, and Engagement

Abstract: This study establishes the relationship among three concepts (attachment, love, and engagement) that have attracted the interest of both practitioners and researchers lately. Based on the consumer-brand relationship literature, a theoretical model is proposed. Using data obtained from a survey to 320 consumers from Madrid (Spain), the results show that only two constructs actually exist: attachment and active engagement, with love being part of attachment (passion) or engagement (long-term relationship). Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
1
15
0
1
Order By: Relevance
“…A considerable amount of research has focused on antecedents and outcomes of brand attachment like brand love, brand engagement (Gómez‐Suárez, 2019), nostalgic emotions (Wen, Qin, & Liu, 2019), product design (Gilal, Zhang, et al, 2020a), loyalty intentions (Hwang, Baloglu, & Tanford, 2019), need satisfaction (Ahn, 2019), and intrinsic motivation (Hung & Lu, 2018). Until now, no single study exists that adequately examines brand attachment as an outcome of firms' CSR activities and/or brand attachment as an antecedent of brand passion.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…A considerable amount of research has focused on antecedents and outcomes of brand attachment like brand love, brand engagement (Gómez‐Suárez, 2019), nostalgic emotions (Wen, Qin, & Liu, 2019), product design (Gilal, Zhang, et al, 2020a), loyalty intentions (Hwang, Baloglu, & Tanford, 2019), need satisfaction (Ahn, 2019), and intrinsic motivation (Hung & Lu, 2018). Until now, no single study exists that adequately examines brand attachment as an outcome of firms' CSR activities and/or brand attachment as an antecedent of brand passion.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Some research (Bıçakcıo glu et al, 2016;Garg et al, 2016) has affirmed that the experience promotes the development of emotional ties with the brand. According to Huang (2017), brand loveand by extension, brand attachment (Moussa, 2015;G omez-Suárez, 2018) have a strong emotional component. Similarly, a study by Japutra et al (2014) revealed that brand attachment is a consequence of experience.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Branding is an important aspect for firms to gain suitable positioning for their products (Palmatier et al, 2017). Brand loyalty is one of the most used aspect of a brand to retain customers and become an incumbent company in the industry (Gómez-Suárez, 2019). Consumer consumption is affected by brand attachment, as proven by the study conducted by Taghipourian & Bakhsh (2015), as it leads to customer's relationship with the brand into a proven behavior of continuous purchase (Baudry, 2016) to fulfil their needs.…”
Section: Introductionmentioning
confidence: 99%